(untitled) (Educação e Pesquisa, 2021)
The work discusses the investigations about the curricular practices within the pedagogical teaching in physical education in high school. Theoretical and methodological discussions are based on the Sociology of the body, everyday life and youth. The study is qualitative, ethnographic-descriptive and the research subjects were the teacher and young students participating in physical education classes, in a public school, in Cuiabá-MT. It involved analysis of documentary sources such as the School’s Pedagogical Project and Annual Physical Education Teaching Plan; participant observations in classes and in the daily life of the school; semi-structured interviews with teacher and young students. Based on the knowledge of aspects of the youth universe, particularly the social markers that permeate the material, cultural and symbolic relationships and conditions of life of the participants, youth can be reflected as a sociocultural category and the relationship of school and physical education within the context of young people’s lives. The absence and presence of meanings in physical education classes were evaluated to reflect on their place in the cultural training project for young people. Possibilities of pedagogical practices that value the teaching of body practices stemming from the approximation to the youth universe are suggested, which is necessary for the legitimacy and pedagogical autonomy of the discipline to occur in the high school curriculum.